Educating Egypt : civic values and ideological struggles - Herrera, Linda, 1964- (The American University in Cairo Press, 2022)
"From the 1952 revolution onward, a main purpose of formal education in Egypt was to socialize the population into adopting certain attitudes and behaviors conducive to the regimes in power. Control by the state over education was never entirely hegemonic, however, due to the persistent influence of foreign actors and Islamist movements. Egyptian education came increasingly under pressure due to a combination of the growing privatization of the education sector, which led to a new class of educational entrepreneurs, the growth of political Islam, which triggered a national security upset, and globalization and rapidly changing digital technologies, which transformed cultures and practices of learning both in and out of the classroom. Educating Egypt traces the everyday practices, policy ideas, and ideological and political battles of education from the era of nation-building in the twentieth century to the age of digital disruption in the twenty-first. Its overarching theme is that schooling and education, broadly defined, have consistently mirrored larger political, economic, and cultural notions about what constitutes the good society and the good citizen, even as these notions have been intensely contested. Drawing on three decades of ethnographic research inside Egyptian schools and among Egyptian youth, Linda Herrera asks what happens when education actors harbor fundamentally different views about the purpose of schooling, the role of the citizen, and the character of the collective "we" of society."--